Comparative Evaluation of Gig Worker and Conventional Worker Welfare to Improve Quality Employment and Encourage Entrepreneurship Using the Propensity Score Matching Approach - Shobikin, Shobikin; Elisabeth, Damarsari Ratnasahara; Wibowo, Teguh Setiawan; Fatchurrohman, Mochamad (LPPM Institut Pendidikan Nusantara Global, 2025)
The development of the digital economy has driven the emergence of gig workers, who are increasingly dominating the labor market. Despite offering flexibility, gig workers continue to face uncertainty regarding welfare conditions, which differ from those of conventional workers. Comparing the welfare of these two groups is essential to provide insights into job quality and its implications for entrepreneurship and inclusive economic development. This study aims to conduct a comparative evaluation of the welfare of gig and conventional workers. Specifically, it seeks to identify the key welfare dimensions that distinguish the two groups and to provide an empirical basis for formulating policies aimed at improving job quality. The research was conducted in the regions of Surabaya, Sidoarjo, Gresik, and Mojokerto, involving 400 respondents, consisting of 200 gig workers and 200 conventional workers. The Propensity Score Matching (PSM) method was employed to ensure comparability of respondents’ characteristics based on age, gender, education level, geographic location, and employment sector, thereby enabling a more valid and reliable comparison of welfare outcomes. The findings reveal that conventional workers enjoy more stable welfare, particularly in terms of income, access to social security, and job security. In contrast, gig workers demonstrate advantages in time flexibility and opportunities to generate additional income. Thus, a trade off emerges between stability and flexibility that differentiates the two types of workers. These results highlight the need for more adaptive labor policies, such as the expansion of social security coverage for gig workers, stronger legal protection, and tailored entrepreneurship development programs. Such measures are expected to enhance multidimensional welfare while fostering the creation of quality jobs in the digital economy era.